2021
DOI: 10.1111/dar.13252
|View full text |Cite
|
Sign up to set email alerts
|

Trends in cocaine use, markets and harms in Australia, 2003–2019

Abstract: Introduction This paper aims to describe cocaine use, markets and harms in Australia from 2003 to 2019. Methods Outcome indicators comprised prevalence of use from triennial household surveys; patterns of use from annual surveys of sentinel samples who use stimulants; and cocaine‐related seizures, arrests, hospitalisations, deaths and treatment episodes. Bayesian autoregressive time‐series analyses were conducted to estimate trend over time: Model 1, no change; Model 2, constant rate of change; and Model 3, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Consequently, younger workers may opt to use more accessible drugs rather than make an active choice to delay use of cocaine 27 ) . Recent studies however have shown that cocaine availability is increasing and becoming easier to obtain in Australia 7 ) and elsewhere 29 ) . Thus, uptake among younger workers may increase and should be monitored in the future, particularly given the slight albeit non-significant reduction in age of cocaine initiation between 2016–2019 (23.9 vs 23.6 years) 5 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, younger workers may opt to use more accessible drugs rather than make an active choice to delay use of cocaine 27 ) . Recent studies however have shown that cocaine availability is increasing and becoming easier to obtain in Australia 7 ) and elsewhere 29 ) . Thus, uptake among younger workers may increase and should be monitored in the future, particularly given the slight albeit non-significant reduction in age of cocaine initiation between 2016–2019 (23.9 vs 23.6 years) 5 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Higher cocaine levels have been accompanied by increased health service utilisation, further underscoring concerns about increased use. Cocaine-related harms, and help-seeking behaviour are illustrated in higher hospitalisation and treatment utilisation rates for cocaine as the principal drug of concern, respectively 7 ) . Cocaine-related mortality has also increased elsewhere in-line with increasing cocaine prevalence 3 , 8 , 9 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, concern regarding methamphetamine use and harms has persisted, and trends following recent investment in treatment have not been explored. Using an approach similar to our recent work in relation to cocaine [19], we examine trends in methamphetamine use, markets and harms using select national data sources from 2003 until 2019.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this issue of Drug and Alcohol Review , Man et al . [13] present a manuscript in which they estimate trends in cocaine use in Australia between 2003 and 2019 using many sources of indicator data. Specifically, they utilise data from: (i) triennial household surveys; (ii) annual surveys of sentinel samples of people who use stimulants; (iii) seizures; (iv) arrests; (v) hospitalisations; (vi) treatment episodes; and (vii) deaths.…”
mentioning
confidence: 99%